Hypothermia Modulates Cytokine Responses After Neonatal Rat Hypoxic-Ischemic Injury and Reduces Brain Damage. (21st November 2014) - Yuan, Xiangpeng; Ghosh, Nirmalya; McFadden, Brian; Tone, Beatriz; Bellinger, Denise L.; Obenaus, Andre; Ashwal, Stephen
While hypothermia (HT) is the standard-of-care for neonates with hypoxic ischemic injury (HII), the mechanisms underlying its neuroprotective effect are poorly understood. We examined ischemic core/penumbra and cytokine/chemokine evolution in a 10-day-old rat pup model of HII. Pups were treated for 24 hr after HII with HT (32℃; n  = 18) or normothermia (NT, 35℃; n  = 15). Outcomes included magnetic resonance imaging (MRI), neurobehavioral testing, and brain cytokine/chemokine profiling (0, 24, 48, and 72 hr post-HII). Lesion volumes (24 hr) were reduced in HT pups (total 74%, p  < .05; penumbra 68%, p  < .05; core 85%, p  = .19). Lesion volumes rebounded at 72 hr (48 hr post-HT) with no significant differences between NT and HT pups. HT reduced interleukin-1β (IL-1β) at all time points ( p  < .05); monocyte chemoattractant protein-1 (MCP-1) trended toward being decreased in HT pups ( p  = .09). The stem cell signaling molecule, stromal cell-derived factor-1 (SDF-1) was not altered by HT. Our data demonstrate that HT reduces total and penumbral lesion volumes (at 24 and 48 hr), potentially by decreasing IL-1β without affecting SDF-1. Disassociation between the increasing trend in HII volumes from 48 to 72 hr post-HII when IL-1β levels remained low suggests that after rewarming, mechanisms unrelated to IL-1β expression are likely to contribute to this delayed increase in injury. Additional studies should be considered to determine what these mechanisms might be and also to explore whether extending the duration or degree of HT might ameliorate this delayed increase in injury.